Review of application of particle image velocimetry (PIV) in assessing hydraulic intake vortex formation characteristics - Aziz N.A.; Zahari N.M.; Zawawi M.H.; Azman A.; Nurhikmah F.; Ramli M.Z.; Ismail I.N.; Abas A. (American Institute of Physics Inc., 2023)
Understanding the nature of the vortex formation is important to research that needs to be cover in order to develop a mitigation plan to avoid or reduce its formation that may cause serious damage to the hydropower mechanical machines. This paper presents a review of significant cases of vortex formation in the hydraulic intake that has been adopted Particle Image Velocimetry (PIV) as a method of the research. The focus of this review is to provide a solid basis for the efficiency of the PIV measurement to study the vortex formation in the hydraulic intake. As a new innovative approach to the vortex study, it stated that PIV is a method that able to find a good agreement and can be validated together with another method. 2020 Author(s).